2018
DOI: 10.1155/2018/5308582
|View full text |Cite
|
Sign up to set email alerts
|

DPP-4 Inhibitors as Treatments for Type 1 Diabetes Mellitus: A Systematic Review and Meta-Analysis

Abstract: Objective Several clinical studies have reported the application of dipeptidyl peptidase-4 (DPP-4) inhibitors as treatments for type 1 diabetes mellitus (T1DM). This study aims to review the outcomes of these existing studies and to discuss the therapeutic effects of DPP-4 inhibitors on T1DM. Methods We thoroughly searched the Medline, Embase, PubMed, and Cochrane Library databases and ClinicalTrials.gov for studies concerning the use of DPP-4 inhibitors in patients with T1DM. Results In preclinical trials, DP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 41 publications
0
28
0
1
Order By: Relevance
“…However, further investigation on downstream signaling was not performed. IL-6 is important for T cell proliferation and Th17 cells show an IL6-dependent increase (Wang et al, 2018;Winer et al, 2009). We have described that CD26 is correlated with augmented Th1 activation along with a marked increase of Th1 cytokines including IL-6.…”
Section: Cd4(+) and Cd8(+) T Cellsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, further investigation on downstream signaling was not performed. IL-6 is important for T cell proliferation and Th17 cells show an IL6-dependent increase (Wang et al, 2018;Winer et al, 2009). We have described that CD26 is correlated with augmented Th1 activation along with a marked increase of Th1 cytokines including IL-6.…”
Section: Cd4(+) and Cd8(+) T Cellsmentioning
confidence: 94%
“…Two studies showed significant HbA1c reduction of −0.27 and − 0.34% after DPP4is treatment for 8 or 4 weeks, respectively (Ellis et al, 2011;Farngren et al, 2012), while the other two studies didn't show any treatment-related differences (Garg et al, 2013;Hari Kumar et al, 2013). A metaanalysis from Wang et al revealed that the additional use of DPP4is results in a greater decrease in HbA1c levels compared to insulin monotherapy, although it is not significant (Wang, Long, et al, 2018).…”
Section: Dpp4/cd26 Inhibition On Autoimmune Diabetesmentioning
confidence: 99%
“…A meta-analysis looking at this topic was published early in 2018 [ 63 ]. Only five trials met the inclusion criteria, which included a total of 253 patients.…”
Section: Dpp-4 Inhibitorsmentioning
confidence: 99%
“…Newer classes of glucose‐lowering therapies for T2D have also been investigated for T1D. A meta‐analysis of five RCTs concluded that the addition of DPP‐4 inhibitors to insulin therapy showed no clear glycaemic benefit for patients with T1D vs insulin monotherapy . An RCT investigating the addition of the GLP‐1RA liraglutide or placebo to insulin therapy in patients with T1D observed greater reductions in A1C, blood glucose concentrations, blood pressure (BP), and body weight with liraglutide .…”
Section: Introductionmentioning
confidence: 99%